EXPERIENTIAL MARKETING, KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN KAFE - Vanesa, Vanesa; Ruslin Chandra , Alhapen; Nurhayati , Nurhayati (ABEC Indonesia, 2023)
One of the culinary businesses that is currently growing significantly in Indonesia is cafe. Consumer behavior when visiting cafes is a very interesting subject to be researched. This study aims to determine the influence of experiential marketing and service quality on customer satisfaction in cafes in the city of Padang. Sample of this study are customers who visited cafes located near the universities in Pauh, Padang, West Sumatra. By using Structural Equation Modeling, it is revealed that the variables of experiential marketing and service quality have a positive and significant impact on customer satisfaction in the cafes.